PENGARUH TEMPERATUR TUANG DAN JENIS MATERIAL AL RONGSOK (PISTON SEPEDA MOTOR DAN KALENG MINUMAN) TERHADAP POROSITAS, KEKERASAN, DAN STRUKTUR MIKRO HASIL PENGECORAN EVAPORATIVE - Muhammad Jurni; Rudi Siswanto (Universitas Lambung Mangkurat, 2019)
Aluminum used many generated from household, workshop, office, factory and so on. All this time, the Al scrap is only collected by the owner and sold to the foundry foundry industry. It can be recycled into various products for various alternative products and has the potential to become a source of business. The evaporative casting method is to use Styrofoam as a pattern dumped in the printed sand. This method will produce castings that match the pattern of Styrofoam made. Melting is done by liquefying Al in a crucible furnace and then poured with a variation of casting temperatur of 650°C, 700°C, 750°C, 800°C. The objective of this research is to know the temperatur of pouring temperatur and material type to micro structure, porosity, and hardness of evaporative casting. The smelting furnace uses a crucible furnace with charcoal wood fuel. Materials used for casting Al scrap piston motorcycles and beverage cans. From the observation of the microstructure shows that the higher temperatur of the dendrite chamber size will change from short thin flakes to flakes. The thicker the thicker the lighter the export the higher and the higher the hardness. Keywords: Evaporative Casting, Effect Of Casting Temperatur